SINTESIS SENYAWA t-KALKON BAHAN DASAR SENYAWA TABIR SURYA - Ruslin Hadanu (Molluca Journal of Chemistry Education (MJoCE), 2018)
A novel method for the synthesis of t-chalcone as material start of sunscreen compounds through aldol condensation reaction was introduced using NaOH/EtOH as a catalyst and solvent. The structures of the t-chalcone of product were confirmed by IR, GC-MS and 1H-NMR spectrosfotometer